Reconsidering the fear of God in Job 37:14-24 and Qohelet 3:1-17 in the light of Rudolf Otto's Das Heilige - Ellis, Ettienne (Old Testament essays, 2015)
This article takes further the work begun in a previous article by investigating the notion of the fear of God in the HB in the light of Rudolf Otto's Das Heilige. The focus of this article is on the usefulness of Otto's views for understanding the meaning and significance of the fear of God in the two wisdom texts of Job 37:14-24 and Qoh 3:1-17. It is argued that taking Otto's views on the mysterium tremendum into account helps to facilitate a greater appreciation of the multifaceted nature of the fear of God in these texts. Maintaining the (creative) tension in the human experience of the divine, put into words most admirably by Otto, is found to be of the importance for the interpretation of Job 37:14-24 and Qoh 3:1-17 - as it may very well also be for other texts of the HB.